Nutrient elements of different agricultural wastes from vermicomposting activity - Sailila, N.; Bakar, A.A.; Mahmood, N.Z.; da Silva, J.A.T.; Abdullah, N.; Jamaludin, A.A. (2010)
Vermicomposting using the earthworm Lumbricus rubellus was conducted for 70 days subsequent to 10 days of pre-composting under glasshouse conditions. Five treatments were used as feed materials with 5 replicates per treatment: T 1 : goat manure, T 2 : paddy straw, T 3 : spent mushroom paddy straw compost, T 4 : sawdust and T 5 : spent mushroom sawdust compost. The treatments were placed in a micro-cosm or worm bin plastic container (360 mm 280 mm 200 mm). The effectiveness of vermicomposting was evaluated through the increment of nutrient elements contained in the vermicompost, growth (biomass weight) and reproduction (total numbers) of earthworms, as a percentage, at the end of the process. The increment of macronutrients in the vermicompost from each treatment was high, especially of organic carbon (C) in T 1 and T 4 , and nitrogen (N), phosphorous (P) and potassium (K) in T 3 . Regarding micronutrients, copper (Cu) had the highest concentration in T 2 and zinc (Zn) in T 1 and T 2 . Therefore, the best vermicompost as a soil fertilizer was T 3 , which showed the highest increment and final content of N (+150.73, 1.50), P (+387.75, 1.06) and K (+886.09, 2.05). There was no significant difference between the number and weight of earthworms among the 5 treatments (P > 0.05). A C: N ratio < 20 indicates the degree of compost maturity and post-vermicomposting, as noted for T 1 and T 3 ; T 1 had the lowest C: N ratio (9.86). Based on our findings, the nutritive value of our vermicompost developed from selected agricultural wastes can be qualitatively assessed as a value-added material against fertilizers or soil stabilizers.